Karakteristik Pasien Penyakit Mata Di RSUD Masohi Maluku Tengah; Studi Deskriptif - George Raden Mas Said; Vanny Leutualy; Saleh Tualeka (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
Maluku is one of the provinces with a fairly high blindness rate in Indonesia. The prevalence of blindness in Maluku was 2.6%, according to the Rapid Assessment of Avoidable Blindness (RAAB) between 2013 and 2017. Some of the causes are cases of uncorrected refraction, cataracts, pterygium, glaucoma, and diseases of the posterior segment of the eye. This study aims to determine the characteristics of eye diseases recorded in Masohi Hospital, Central Maluku. This study uses a quantitative method through a retrospective approach. Data collection was conducted through patient medical records at Masohi Hospital, Central Maluku, from January 2019Â to December 2020. The results of data analysis showed that there were 852 new patient visits throughout 2019 and 465 people in 2020. The prevalence of cases was mostly found in women in 2019 and 2020. Masohi City District is the sub-district with the highest number of eye patients, followed by Amahai District. The most cases in 2019 included refraction, cataract, pterygium and asthenopia. While in 2020, refraction was the most cases, followed cataract, pterygium and asthenopia.Keywords: Blindness; characteristics of eye diseases; visual disturbances